Pengaruh metode massage terhadap pengurangan intensitas nyeri pada persalinan kala I - Emilda AS; Elfida Elfida; Fazdria Fazdria (Jurnal Kesehatan Ibu dan Anak, 2014)
Pain during labor is a thing that makes women feel anxious .Assume that pain is a physiological process that even the other type of pain that is always caused by an accident or illness , Massage is one of the non-pharmacologicalmethods are done to relieve labor pain. Objective: To determine the effect of method of Massage Pain Intensity Reduction In the first stage of labor in the Delivery RoomGeneral Hospital Aceh Tamiang" .This research is to design Analytic Cross - Sectional .The population in this study were all mothers giving birth in Delivery Room Hospital Aceh Tamiang , the way sampling is birthing mothers when I. Sampling collection techniques by accidental sampling.The results showed that of the 45 respondents obtained at the time (post - treatment) the majority of respondents 28 (62,2%) experienced pain Serious . Meanwhile, after the massage intervention effiuerage (Post - treatment) showed Kala Pain Intensity I Persalian majority 21(46.7%) respondents experiencedModerate Pain. And the results of analysis of the Paired T -test is obtained (value P value 0.000) . it can be concluded that there are significant differences in the reduction of painintensity in the first stage of labor after themassage action onmaternal parturition.Massegecanused as one of the interventions in reducing pain active phase of the first stage of labor, as an alternative non pharmacological techniques for Midwifery Education.